Research of the business aviation market services - Хлопіна-Квіч, Ольга Іванівна (Technology audit and production reserves, 2013)
In the article the author considered state of the modern Ukrainian market of business aviation services and prospects of its development. Estimated are the main advent principal of possessing own fleet of small aircraft and analysis is made its structure. Explored is the dynamics of organizing business aircraft flights in Ukraine. Proposed is the list of variables, which will allow to evaluate the state of the market of small aviation services. Such variables are: general structure of the market of small aviation services; share of value of business aviations’ services; degree of satisfaction of consumers ’ needs; conditions and efficiency of business aviation aircraft; operation degree of passengers activity on board of business and passenger airplane; flexibility and degree of individualization of the flights organization of business aviation; the time spent on flight registration.